Cytotoxicity of Portland Cement with Different Radiopacifying Agents: A Cell Death Study - Gomes Cornelio, Ana Livia [UNESP]; Salles, Loise Pedrosa [UNESP]; da Paz, Mariana Campos; Cirelli, Joni Augusto [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru Filho, Mario [UNESP] (Elsevier B.V., 2011)
Introduction: The aim of this study was to investigate the cytotoxicity of white Portland cement (PC) alone or associated with bismuth oxide (PCBi), zirconium oxide (PCZir), and calcium tungstate (PCCa) in 2 cell lineages. Methods: Murine periodontal ligament cells (mPDL) and rat osteosarcoma cells (ROS 17/2.8) were exposed for 24 hours to specific concentrations of fresh PC and PC associations with radiopacifiers. Zinc oxide-eugenol cement and hydrogen peroxide treatment were applied as cytotoxic positive controls. Cell viability after incubation with the cements was assessed by mitochondrial dehydrogenase enzymatic assay. Cell morphology was microscopically analyzed by cresyl violet staining, and the mechanism of cell death was determined by acridine orange/ethidium bromide methodology. All data were analyzed statistically by analysis of variance and Tukey post hoc test (P < .05). The correlation among cell death by apoptosis or necrosis and pH values was established by Pearson linear coefficient. Results: The mitochondrial dehydrogenase enzymatic assay only revealed significant cell death rate at high concentrations of cement elutes. PC alone was not cytotoxic, even at 100 mg/ml. Microscopic images showed that none of the PC formulations caused damage to any cell lines. Statistical analysis of apoptosis/necrosis data demonstrated that PC and PC plus radiopacifying agents promoted significant necrosis cell death only at 100 mg/mL. Conclusions: The mPDL cells were more sensitive than ROS17/2.8. The results showed that PC associated with bismuth oxide, zirconium oxide, or calcium tungstate is not cytotoxic to mPDL or ROS17/2.8. Zirconium oxide and calcium tungstate might be good alternatives as radiopacifying agents. (J Endod 2011;37:203-210)
Keywords: Apoptosis; cytotoxicity; Portland cement; radiopacifying agent